Sensible and Latent Heat Fluxes and Humidity Profiles Following a Step Change in Surface Moisture - Andreas,Edgar L (1982)
From a high-quality set of velocity, temperature, and humidity profiles collected upwind and downwind of a step change in surface roughness, temperature, and moisture, we have calculated upwind and downwind values of the heat fluxes and friction velocity. The surface change is from smooth to rough; upwind, the sensible heat flux is upward and the latent heat flux is zero; downwind, the surface is well-watered so that the latent heat flux is upward while the sensible heat flux is downward. The downwind latent heat flux in this fetch-limited flow obeys NL=0.08 Rx 0.76 where NL is the latent heat Nusselt number and Rx is the fetch Reynolds number, a parameter for characterizing fetch-limited flows. Because this relation is virtually the same as one found to describe the sensible heat and condensate fluxes over arctic leads, we conclude that the Nusselt numbers nondimensionalizing scalar fluxes are the same for a given fetch Reynolds number when boundary conditions are similar.